Placental volume and vascularization flow indices by 3D power Doppler US using VOCAL technique and correlation with IGF-1, free beta-hCG, PAPP-A, and uterine artery Doppler at 11-14 weeks of pregnancy - (:unkn) unknown (WALTER DE GRUYTER GMBH, 2011)
Aims: The purpose of this study was to investigate correlations between first trimester placental volume (PV) and blood flow indexes (FIs), bilateral uterine artery pulsatility indexes, notching, and biochemical parameters: pregnancy-associated plasma protein-A (PAPP-A), free beta-human chorionic gonadotropin (f-beta-hCG), and insulin-like growth factor-1 (IGF-1) to predict the high-risk pregnancies in the first trimester. Methods: We prospectively examined 310 patients at 11-14 weeks of pregnancy using transabdominal 3D gray scale and power Doppler ultrasound for assessing PV, vascularization index, FI, and vascularization FI (VFI). The acquired volumes were analyzed using VOCAL (TM) imaging software. The results were correlated with biochemical parameters. Results: We found significant correlations between PV and biochemical parameters, and between placental blood flow studies and other parameters. Finally, PV/crown-rump length so called the placental quotient is also related to both PAPP-A and VFI. Conclusions: Placental volumetry, uterine artery Doppler studies, blood flow calculations and biochemical parameters, such as f-beta-hCG, PAPP-A, and IGF-1 could be important in the early and rapid diagnosis of high-risk pregnancies. Thus, they may be useful in first trimester prediction of fetal growth restriction presenting with alterations in PV and vascularity.
Keywords: first trimester pregnancy; free beta-human chorionic gonadotropin; insulin-like growth factor-1; intrauterine growth retardation; placental vascularization; placental volume; pregnancy-associated plasma protein-A; three-dimensional (3D) power Doppler ultrasound; uterine artery doppler ultrasonography; VOCAL; FETAL-GROWTH RESTRICTION; PLASMA-PROTEIN-A; FOR-GESTATIONAL-AGE; 3-DIMENSIONAL ULTRASOUND; 1ST TRIMESTER; TROPHOBLAST DIFFERENTIATION; 2ND TRIMESTER; IN-VITRO; PREECLAMPSIA; COMPLICATIONS